Analisis Tingkat Pemahaman Mahasiswa Terhadap PSAK No.101 Laporan Keuangan Syariah (Studi Pada Mahasiswa Akuntansi Syariah IAIN Syaikh Abdurrahman Siddik Bangka Belitung) - Fitaloka, Dewi Galu; Wulpiah, Wulpiah; Marheni, Marheni (JYRS: Journal of Youth Research and Studies, 2022)
Understanding is a student’s ability to define things and comprehend can make sense of the things contained in both a theory and concepts learned. This study discusses the level of understanding of Islamic accounting study program students against PSAK No.101 Islamic Financial Report at IAIN Syaikh Abdurrahman Siddik Bangka Belitung. This problem is viewed from active students of the Islamic Accounting Study Program for the 2018-2019 batch. The data analysis used research is descriptive quantitative with the aim of revealing the state or characteristics of the sample data for the research variables. The primary data source is by distributing questionnaire through Google Form consists of 20 questions. The sample’s 96 active students of the Islamic Accounting Study Program for the 2018-2019 school year. This study used a purposive sampling technique because the sample was only a course the Islamic Financial Accounting Course. The data processing is Microsoft Excel and IBM SPSS version 26 software with index and interval tests and converts them into scores based on the Student Understanding Index assessment standards. The results showed that the overall average value of the test index conducted by Islamic Accounting students was 49,96% of students in the "Less Understand" category or the overall average value of the test intervals conducted by Islamic Accounting students was 2.50 students in the "Low" category understanding PSAK No. 101 Islamic Financial Report.